Adsorption of chlorine from drinking water by granular activated carbon - Al-Mamun, Abdullah; Salleh, Md. Noor; Al-Edresi, Esam Abdo Ali (2014)
The effects of GAC dosage, contact time, agitation speed and the initial concentration of free chlorine were investigated at the room temperature ranges between 23-27˚C with a constant pH of 7.0±0.10. The statistical optimization of the experimental condition was carried out using Central Composite Design (CCD) to develop the regression models for the optimum adsorption process condition. The study was furthered to determine the interaction between the parameters involved. This study also compared the adsorption of chlorine using acid washed GAC and non-acid washed GAC. The adsorption study has demonstrated that the highest removal of free chlorine using acid washed GAC is 55% and for non-acid washed GAC is 85%. Furthermore, it was determined that the optimum conditions for maximum removal of free chlorine was for acid washed GAC, pH (7.0±0.10), agitation speed (100 rpm), contact time (50 minutes) and GAC dosage (1g/L) and for non-acid washed GAC, pH (7.0±0.10), agitation speed (300 rpm), contact time (10 minutes) and GAC dosage (1 g/L). It was also demonstrated that non-acid washed GAC has higher adsorption capacity (0.12 mg/g) whereas acid washed GAC has a lower adsorption capacity of (0.021 mg/g). Therefore, it can be concluded that the residual chlorine from potable water is better removed by the non-acid washed GAC due to the larger surface area in comparison to the acid washed GAC.